Challenging Issues on Paranasal Sinuses 2019
DOI: 10.5772/intechopen.79376
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Metopic Suture Persistence and Frontal Sinus Development

Abstract: The frontal bone develops as two halves, which further unite in a single bone by the closure of the mid-sagittal metopic suture, typically by the end of the first postnatal year. The frontal sinus begins to expand into the orbital and vertical plates of the frontal bone postnatally and reaches the level of the nasion by the fourth year of age. At this time, the metopic suture is usually entirely closed. However, in the cases of failed closure of the metopic suture, its relationship to the frontal sinus develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In this case, the cranium is of medium size without any obvious deformations in its shape and size. Metopism is frequently associated with underdevelopment of the frontal sinus [17,19,20,23,24]. However, in the reported case all paranasal sinuses are well-developed.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this case, the cranium is of medium size without any obvious deformations in its shape and size. Metopism is frequently associated with underdevelopment of the frontal sinus [17,19,20,23,24]. However, in the reported case all paranasal sinuses are well-developed.…”
Section: Discussionmentioning
confidence: 69%
“…Metopic crania have distinctive cranial morphology [26,27,29] with frequently manifested supernumerary calvarial bones, remnants from embryonic sutures [9,21,26,35] and underdeveloped frontal sinus [23,24]. They demonstrate a general delay in calvarial sutures closure [28] and a wide array of midline closure defects [37].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is some evidence that a complete persistent metopic suture affects the presence and/or size of a frontal sinus (Guerram et al, 2014;Nikolova et al, 2016Nikolova et al, , 2018 Despite the claim by Bilgin et al (2013) that no reasonable explanation has been provided for this association, it is perhaps a reasonable expectation insofar as a complete suture extending from nasion to bregma will result in a wide separation of the left and right pneumatic spaces. On the other hand, while the suture itself should theoretically not affect the superior expansion of either sinus, there may be an indirect relationship between a persistent metopic suture and sinus size if the mechanisms that result in persistent metopism also affect the development of the frontal sinuses (Nikolova et al, 2019). Regardless, and in light of the evidence published to date, we excluded two (2) individuals (both female) who exhibited persistent full metopism from the sample.…”
Section: Excluded Crania-the Final Samplementioning
confidence: 99%
“…The unusual obliteration of the squamous suture has been found to be related to slight bilateral differences in the middle and posterior part of the neurocranium (Nikolova et al, 2021a). It has also been found that the condition of a bipartite frontal bone in adult individuals, known as metopism, is related to specific characteristics including frontal sinus underdevelopment (Nikolova et al, 2018a(Nikolova et al, , 2018b, significant delay of sagittal suture closure (Nikolova et al, 2022a), supernumerary bones (Hanihara and Ishida, 2001a;Nikolova et al, 2016Nikolova et al, , 2020, and modification of cranial morphology (Nikolova et al, 2021b(Nikolova et al, , 2022b. Metopism has been reported to occur in different population groups with varying frequencies from 0% to exceeding 15% (Berry and Berry, 1967;Hauser and De Stefano, 1989;Hanihara and Ishida, 2001a;Zdilla et al, 2018) The squamous part of the occipital bone is composed of interparietal and supraoccipital parts.…”
Section: Introductionmentioning
confidence: 99%